ANALISIS EFISIENSI BIAYA USAHATANI PADI SAWAH (Oryza sativa L.) DI DESA BUKIT RAYA KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA (Analysis of Cost Efficiency of Wetland Paddy Farming (Oryza sativa L.) in Bukit Raya Village Tenggarong Seberang Subdistrict Kutai Kartanegara District) - NIKE LAWUNING TIYAS; NDAN IMANG; MUHAMMAD ERWAN SURIAATMAJA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2018)
Farming activities must take into account the costs incurred for the production factors used. This needs to be considered by farmers in order to be able to use the inputs cost of production efficiently in managing their farming. The purposes of this study were to determine the effect of production costs in the form of planting area, seeds, fertilizers, pesticides, and laborers on revenue of wetland paddy farming and to find out the cost efficiency of wetland paddy farming in Bukit Raya Village, Tenggarong Subdistrict, Kutai Kartanegara District. This research was conducted from April to July 2018. Samples were taken by using the propotionate stratified random sampling method with a total sample of 41 respondents. The analysis technique used  the production function of Stochastic Frontier SFA to determine the effect of production costs in the form of planting area, seeds, fertilizers, pesticides, and laborers on revenue of wetland paddy farming and to find out the cost efficiency of wetland paddy farming. The cost of production factors has a significant effect on revenue of wetland paddy farming. The cost of seeds, fertilizers, and pesticides have no effect. Analysis of the cost efficiency of wetland paddy farming showed that farming did not efficient with an average efficiency level of 1.46 because farmers did not manage inputs cost efficiently.